Antimicrobial, antioxidant and essential oil studies on Veratrum album L. (Melanthiaceae) - Sancar, Pelin Yılmaz; İnci, Şule; Demirpolat, Azize; Kırbağ, Sevda; Civelek, Şemsettin (Pamukkale University, 2024)
In this study, essential oil components of the Veratrum album L. and the antimicrobial and antioxidant properties of these components were determined. The chemical composition of the essential oils of dried aerial parts of V. album was analyzed using GC and GC-MS. Antimicrobial activity was determined with the disk diffusion method. Total antioxidant status (TAS), total oxidant status (TOS) and 2.2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity were detected for the antioxidant activity of the plant. According to the analysis results, the major essential oil components of the V. album were determined as hexacosane (39.5%), myristic (tetradecanoic) acid (22.8%), heptane (6.5%), anethole (4.9%) and 1,8- cineole (4.8%). The findings showed that the methanol extracts of the stem and leaf parts of the plant inhibited the growth of pathogenic microorganisms at different rates (14±0.1 - 34±0.3 mm). The TAS values of methanol extracts of stem and leaf parts of V. album were calculated as 3.75±0.07 and 3.91±0.01 mmol, while TOS values were calculated as 6.14±0.13 and 6.54±0.05 ?mol. The scavenging activity of the DPPH radical increased depending on increasing concentrations of the plant extract. © The Author(s) 2024. Open Access This article is licensed under a Creative Commons Attribution 4.0 International License.
Keywords: Antimicrobial activity; Antioxidant activity; Essential oil composition; Türkiye; Veratrum album